Analisa Audit Sistem Informasi Barang Atau Jasa PT. Jaya Karya Menggunakan COBIT 5.0 - Diaz Kuncoro; Mairani Mairani; Novi Yunanda Putri (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
An audit needs to be carried out so that an information system is able to meet IT Governance requirements. PT. Jaya Karya is a company operating in the field of goods delivery services that has used information systems to support its business processes for the last 4 years. It is time now to carry out an audit of the goods delivery information system This is so that we can find out whether the information system implemented is in accordance with the vision, mission and goals of the organization as well as testing the performance of the information system. In this research, an analysis of the goods delivery information system at PT. Jasa Karya Palembang branch uses the COBIT 5.0 framework with sub domain MEA01 (Monitor, Evaluate, and Assess Performance and Conformance) with process capability level calculations and also analysis of Strength, Weakness, Opportunity and Threats (SWOT), Internal Factor Analysis Summary (IFAS) , as well as External Factor Analysis Summary (EFAS)). Data was obtained through observation techniques, interviews, literature study. Respondents for the data consisted of Branch Heads, Operations Managers and Operational Staff.